Choledocholithiasis: when to Suspect, how to Diagnose, how to Treat - Aleknaitė, Aušra; Simutis, Gintaras (Lietuvos chirurgija, 2019)
Bile duct stones are a quite common (10–18%) complication of gallstone disease or an autonomous condition. New noninvasive diagnostic methods established in the last decades allow to confirm suspected choledocholithiasis with minimal risk of iatrogenic complications.In this literature review we discuss various scores for choledocholithiasis risk degree, different diagnostic investigations and management approaches including timing for invasive procedures.
Keywords: choledocholithiasis; common bile duct stones; laparoscopic cholecystectomy; endoscopic retrograde cholangiopancreatography (ERCP); intraoperative cholangiography; endoscopic ultrasound; magnetic rezonance cholangiopankreatography